THE ROLE OF ECOLOGICAL COMPETENCE IN THE MORAL DEVELOPMENT OF MEDICAL EDUCATION STUDENTS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article analyzes the phraseological units encountered in Togaymurod’s Otamdan qolgan dalalar. The study examines the lexical-semantic features, artistic functions, and the role of these phrases in character creation. The analysis highlights the expressive, emotional, and national-mentality-specific layers of these phrases.